2012
DOI: 10.1111/j.1442-200x.2011.03521.x
|View full text |Cite
|
Sign up to set email alerts
|

Cord serum adiponectin is positively related to postnatal body mass index gain

Abstract: Birthweight SD score, gestational age, and cord serum adiponectin levels are significant predictors of BMI Z-score gain from birth to 3 years of age in Japanese infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
2
12
0
1
Order By: Relevance
“…Nakano et al (17) found that adiponectin levels in cord serum significantly predict body mass index (BMI) z-score gains from birth to 3 years of age in Japanese infants; however, when only the first 6 months were analysed, it was found that adiponectin levels do not predict postnatal BMI z-score gains, a finding that suggests that energy intake influenced by breast feeding and leptin levels may be stronger factors that affect changes in BMI z-scores than adiponectin levels during this period. Meanwhile, Mazaki-Tovi et al (13) reported that adiponectin concentrations negatively correlate with weight and BMI at one year of age, and that leptin concentrations positively correlate with weight and size at one year, suggesting the role of both adipokines in postnatal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Nakano et al (17) found that adiponectin levels in cord serum significantly predict body mass index (BMI) z-score gains from birth to 3 years of age in Japanese infants; however, when only the first 6 months were analysed, it was found that adiponectin levels do not predict postnatal BMI z-score gains, a finding that suggests that energy intake influenced by breast feeding and leptin levels may be stronger factors that affect changes in BMI z-scores than adiponectin levels during this period. Meanwhile, Mazaki-Tovi et al (13) reported that adiponectin concentrations negatively correlate with weight and BMI at one year of age, and that leptin concentrations positively correlate with weight and size at one year, suggesting the role of both adipokines in postnatal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous longitudinal investigations have been based on cord blood or maternal levels of adipokines during pregnancy . While these concentrations were impacted by placental production, our dried blood spot concentrations are not as both adiponectin and leptin have short half‐lives .…”
Section: Discussionmentioning
confidence: 80%
“…Another study found no associations with rapid infant weight gain at 3 months ( n = 340) with respect to maternal levels of adiponectin measured by fasting serum taken at time of oral glucose tolerance test regardless of whether the pregnancy was complicated by gestational diabetes . Among 56 Japanese infants, cord serum adiponectin levels were associated with weight gain from birth to 3 years of age but not with BMI z‐scores at cross‐sectional time points of 6, 12, and 36 months . One study made similar observations with more direct measures of adiposity .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations